AtCesA8-driven OsSUS3 expression leads to largely enhanced biomass saccharification and lodging resistance by distinctively altering lignocellulose features in rice - Fan, Chunfen (Biotechnol Biofuels, 2017)
BACKGROUND: Biomass recalcitrance and plant lodging are two complex traits that tightly associate with plant cell wall structure and features. Although genetic modification of plant cell walls can potentially reduce recalcitrance for enhancing biomass saccharification, it remains a challenge to maintain a normal growth with enhanced biomass yield and lodging resistance in transgenic plants. Sucrose synthase (SUS) is a key enzyme to regulate carbon partitioning by providing UDP-glucose as substrate for cellulose and other polysaccharide biosynthesis. Although SUS transgenic plants have reportedly exhibited improvement on the cellulose and starch based traits, little is yet reported about SUS impacts on both biomass saccharification and lodging resistance. In this study, we selected the transgenic rice plants that expressed OsSUS3 genes when driven by the AtCesA8 promoter specific for promoting secondary cell wall cellulose synthesis in Arabidopsis. We examined biomass saccharification and lodging resistance in the transgenic plants and detected their cell wall structures and wall polymer features. RESULTS: During two-year field experiments, the selected AtCesA8::SUS3 transgenic plants maintained a normal growth with slightly increased biomass yields. The four independent transgenic lines exhibited much higher biomass enzymatic saccharification and bioethanol production under chemical pretreatments at P < 0.01 levels, compared with the controls of rice cultivar and empty vector transgenic line. Notably, all transgenic lines showed a consistently enhanced lodging resistance with the increasing extension and pushing forces. Correlation analysis suggested that the reduced cellulose crystallinity was a major factor for largely enhanced biomass saccharification and lodging resistance in transgenic rice plants. In addition, the cell wall thickenings with the increased cellulose and hemicelluloses levels should also contribute to plant lodging resistance. Hence, this study has proposed a mechanistic model that shows how OsSUS3 regulates cellulose and hemicelluloses biosyntheses resulting in reduced cellulose crystallinity and increased wall thickness, thereby leading to large improvements of both biomass saccharification and lodging resistance in transgenic rice plants. CONCLUSIONS: This study has demonstrated that the AtCesA8::SUS3 transgenic rice plants exhibited largely improved biomass saccharification and lodging resistance by reducing cellulose crystallinity and increasing cell wall thickness. It also suggests a powerful genetic approach for cell wall modification in bioenergy crops. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13068-017-0911-0) contains supplementary material, which is available to authorized users.